Penggunaan Tugas Terstruktur Prapembelajaran untuk Meningkatkan Motivasi Belajar Siswa - Ibnu Sugeng Riyadi (Pusat Riset dan Inovasi Nasional, 2023)
Based on the observations and experiences of researchers at SMK Negeri 1 Cidaun, especially the Freshwater Fisheries Agribusiness expertise program, student motivation in participating in the learning process is still very low. The purpose of this study was to increase students' learning motivation by using the method of giving pre-learning structured assignments. The research was conducted using three cycles of classroom action research in class XII APAT of SMK Negeri 1 Cidaun in the 2022/2023 academic year. Based on the results of observations, it is known that there is an increase in student learning motivation in each learning cycle that is carried out. This is shown by the increasing percentage of positive activities carried out by students in participating in learning.